Crafting a performance-focused strategy of "Deep Purpose". Issue 3 (1st April 2022) - Denning, Stephen
Abstract : Purpose: Research has found that firms with deep purpose treat purpose as an existential intention that informed every decision, practice and process. They adopted purpose as their operating system, perceiving it as a vital animating force. As a result, they navigated the tumultuous terrain of multi-stakeholder capitalism far more adeptly than most, increasing value for all stakeholders, including investors, over the long-term. Design/methodology/approach: The author analyses Professor Ranjay Gulati's new book "Deep Purpose" and his HBR article, "The Messy but Essential Pursuit of Purpose" that introduce the concept of "deep purpose, " which has enabled some firms to "operate with heightened passion, urgency, and clarity". Findings: Firms with deep purpose treat 'purpose as an existential intention that informed every decision, practice and process'. Practical/implications: Purpose serves as an organizing principle that shapes decision-making and binds stakeholders to one another. Originality/value: This is a very timely article that will held senior executives develop and articulate their firms purpose statement and connect it to their operating practices.